Sleep medicine catalogue of knowledge and skills – Revision. (27th May 2021) - Penzel, Thomas; Pevernagie, Dirk; Bassetti, Claudio; Peigneux, Philippe; Paunio, Tiina; McNicholas, Walter T.; Dogas, Zoran; Grote, Ludger; Rodenbeck, Andrea; Cirignotta, Fabio; d'Ortho, Marie‐Pia; Nobili, Lino; et al.
Abstract: The 'catalogue of knowledge and skills' for sleep medicine presents the blueprint for a curriculum, a textbook, and an examination on sleep medicine. The first catalogue of knowledge and skills was presented by the European Sleep Research Society in 2014. It was developed following a formal Delphi procedure. A revised version was needed in order to incorporate changes that have occurred in the meantime in the International Classification of Sleep Disorders, updates in the manual for scoring sleep and associated events, and, most important, new knowledge in sleep physiology and pathophysiology. In addition, another major change can be observed in sleep medicine: a paradigm shift in sleep medicine has taken place. Sleep medicine is no longer a small interdisciplinary field in medicine. Sleep medicine has increased in terms of recognition and importance in medical care. Consequently, major medical fields (e.g. pneumology, cardiology, neurology, psychiatry, otorhinolaryngology, paediatrics) recognise that sleep disorders become a necessity for education and for diagnostic assessment in their discipline. This paradigm change is considered in the catalogue of knowledge and skills revision by the addition of new chapters.